2021
DOI: 10.3390/ijms22126296
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nuclear Factor of Activated T Cells 5 in Hyperosmotic Stress-Exposed Human Lens Epithelial Cells

Abstract: We investigated the role of nuclear factor of activated T cells 5 (NFAT5) under hyperosmotic conditions in human lens epithelial cells (HLECs). Hyperosmotic stress decreased the viability of human lens epithelial B-3 cells and significantly increased NFAT5 expression. Hyperosmotic stress-induced cell death occurred to a greater extent in NFAT5-knockout (KO) cells than in NFAT5 wild-type (NFAT5 WT) cells. Bcl-2 and Bcl-xl expression was down-regulated in NFAT5 WT cells and NFAT5 KO cells under hyperosmotic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…7 B, Additional file 13 : Table S9B). Consistently, previous studies revealed a role for NFAT5 in the hyperosmotic stress response in human lens epithelial cells [ 85 ], SOX2 is a well-established transcription factor required for lens development [ 90 ], and the MAF family of transcription factors are known regulators of lens gene expression and lens development [ 76 , 77 , 79 81 ]. The data suggest that changes in DNA methylation within the identified regions regulate the ability of specific lens transcription factors to control gene expression changes during lens cell differentiation.…”
Section: Resultssupporting
confidence: 76%
“…7 B, Additional file 13 : Table S9B). Consistently, previous studies revealed a role for NFAT5 in the hyperosmotic stress response in human lens epithelial cells [ 85 ], SOX2 is a well-established transcription factor required for lens development [ 90 ], and the MAF family of transcription factors are known regulators of lens gene expression and lens development [ 76 , 77 , 79 81 ]. The data suggest that changes in DNA methylation within the identified regions regulate the ability of specific lens transcription factors to control gene expression changes during lens cell differentiation.…”
Section: Resultssupporting
confidence: 76%
“…We thus aimed to thoroughly investigate the mechanisms from an autophagy perspective, which is a direction relatively untouched given that previous studies mainly focused on the protein changes for this topic. We adopted a stricter standard of 600 mOsm for 6h, which studies have proven would lead to significant apoptosis of epithelial cells, leaving only a small number of functional cells [13][14] . This would minimize the chances of cells remaining viable by chance, helping us identify significant characteristics and mechanisms that would prevent apoptosis under an extreme hyperosmotic environment.…”
mentioning
confidence: 99%